Empirical Evidence from the Indonesia Stock Exchange: The Influence of Debt to Equity Ratio (DER) and Return on Equity (ROE) on Sharia Stock Prices - Sri Bulkia; Burhannudin; Kurniaty Kurniaty; Alpia Rahmah; Mustaghfiri Abdan (Ilomata International Journal of Tax and Accounting, 2022)
This paper aims to obtain empirical evidence about the influence of the Debt to Equity Ratio (DER) and Return on Equity (ROE) on Islamic stock prices, either partially or simultaneously. An exploratory investigation of 26 companies classified as sharia with the criteria of the Jakarta Islamic Index on the Indonesia Stock Exchange. The secondary data analysis used is to collect complete financial data for the 2014-2018 period. The secondary data was successfully examined as many as 130, then processed using SPSS 26, then analyzed using regression. The findings of the investigation provide empirical evidence that the Debt to Equity Ratio (DER) and Return on Equity (ROE) have a positive and significant influence on Islamic stock prices, either partially or simultaneously. This study provides a theoretical contribution to limited research exploring the Debt to Equity Ratio (DER) and Return on Equity (ROE) with Islamic stock prices on the stock exchange in Indonesia. In practice, this research provides significant insights that can be used to measure the company's health and assess the company's ability to generate returns from shareholder investments of companies classified as sharia.